Transformation of Rural Landscape in the Southern Part of the Province of Dalmatia: Polače, Ostrvica, Mogorjelo - Turković, Tin; Maraković, Nikolina (2012)
Three case studies were chosen by the authors in order to demonstrate the processes of transformation of the countryside in the coastal region of the Roman province of Dalmatia. The authors have given their interpretations of the buildings and their purpose, and also proposed their dating of the structures.
ENG